2019
DOI: 10.1007/s00429-018-01824-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic labeling reveals temporal and spatial expression pattern of D2 dopamine receptor in rat forebrain

Abstract: The D2 dopamine receptor (Drd2) is implicated in several brain disorders such as schizophrenia, Parkinson’s disease, and drug addiction. Drd2 is also the primary target of both antipsychotics and Parkinson’s disease medications. Although the expression pattern of Drd2 is relatively well known in mouse brain, the temporal and spatial distribution of Drd2 is lesser clear in rat brain due to the lack of Drd2 reporter rat lines. Here, we used CRISPR/Cas9 techniques to generate two knockin rat lines: Drd2::Cre and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 71 publications
(83 reference statements)
1
33
0
Order By: Relevance
“…D2/3 receptors are also differentially expressed in PFCx and their activation contribute to specific cognitive processes ( Robinson and Sohal, 2017 ; Bailey et al., 2020 ; Papenberg et al., 2020 ). D2 are enriched within subcortically projecting L5 pyramidal neurons thick-tufted pyramidal cells, with projections to thalamus and pons, but not contralateral cortex ( Yu et al., 2019 ). These neurons exhibit a prominent hyperpolarization-activated cationic current.…”
Section: Section 2: Dr Alterations In Schizophreniamentioning
confidence: 99%
“…D2/3 receptors are also differentially expressed in PFCx and their activation contribute to specific cognitive processes ( Robinson and Sohal, 2017 ; Bailey et al., 2020 ; Papenberg et al., 2020 ). D2 are enriched within subcortically projecting L5 pyramidal neurons thick-tufted pyramidal cells, with projections to thalamus and pons, but not contralateral cortex ( Yu et al., 2019 ). These neurons exhibit a prominent hyperpolarization-activated cationic current.…”
Section: Section 2: Dr Alterations In Schizophreniamentioning
confidence: 99%
“…This indicates a functional role of dopamine in the entire OB, including the glomerular layer as well as in external plexiform layer, which is consistent with our results. The distribution of the D 2 receptor has its highest density in the GL and nerve layer, while D 2 receptor expression in the EPL is sparse 40,[43][44][45] . Despite that, the dopamine-induced calcium transients where strongly reduced in the presence of D 2 antagonist sulpiride in both the GL and EPL, indicating expression of D 2 receptors in astrocytes of the EPL.…”
Section: Scientific Reports |mentioning
confidence: 99%
“…Surprisingly, despite the wealth of studies on the dopaminergic system, very little is known about D2R expression in the hippocampus proper (Gasbarri et al, 1997; Beaulieu and Gainetdinov, 2011); most studies to date, focused on the basal ganglia and occasionally on the frontal cortex (Levey et al, 1993; Yung et al, 1995; Santana et al, 2009; Lavian et al, 2018). The most extensive examination of D2R expression in rat hippocampus up to now was performed by Yu et al (2019). In their work they showed that D2R is mainly expressed in cells of the Stratum pyramidale (sp) and Stratum radiatum (sr) layers of the CA1–3 regions, in the dentate gyrus (DG), and in axon terminals innervating the Stratum lacunosum-moleculare (slm) of the CA1 of the dorsal hippocampus.…”
Section: Introductionmentioning
confidence: 99%